Design and Build a Video Streaming Application using a Minimum Viable Product (MVP) - Ricky Sebastian Irawan; Sharon Han; Arif Tirtana (LPPM STIKI Malang, 2022)
Covid-19 makes people's mobility very limited. Because the mobility and capacity of an event is very limited, it makes many events forced to be postponed or even canceled because to prevent the spread of the Covid-19 virus from increasing. Some media eventually became a solution to the problem. One of them is video streaming media. Video streaming media is very helpful for organizers to provide information and impressions of the event via the internet. So that the audience does not need to come to the venue directly. This also makes it easier for viewers who are outside the city or even abroad to follow the event directly. STIKI Basketball League (SBL) has used this solution to limit these problems. The absence of spectators makes the venue even more lonely and boring due to building capacity restrictions which make supporters unable to support their team directly on the spot, but they can still support through video streaming media provided by the organizer. The video streaming media is also sold on a website that functions so that viewers who want to access their team's matches must subscribe first. The website product is packaged by the organizer using the Minimum Viable Product (MVP) concept which aims to make it easier for the audience to understand what features are sold by the committee. Thus, the presence of MVP in the product can increase the income from the event.